On the reliability of the Old Testament - Kitchen, Kenneth Anderson (Grand Rapids, MI Eerdmans, 2003)
Includes bibliographical references, indexes, plates, maps, diagrams.
Keywords: Bible. O.T. -- evidences, authority, etc; Bible. O.T. -- history of biblical events